Changes in Systemic Regulatory T Cells, Effector T Cells, and Monocyte Populations Associated With Early-Life Stunting - Andriamanantena, Zo; Randrianarisaona, Fanirisoa; Rakotondrainipiana, Maheninasy; Andriantsalama, Prisca; Randriamparany, Ravaka; Randremanana, Rindra; Randrianirina, Frédérique; Novault, Sophie; Duffy, Darragh; Huetz, François; Hasan, Milena; Schoenhals, Matthieu; et al. (Frontiers in Immunology, 2022)
Stunting and environmental enteric dysfunction (EED) may be responsible for altered gut and systemic immune responses. However, their impact on circulating immune cell populations remain poorly characterized during early life. A detailed flow cytometry analysis of major systemic immune cell populations in 53 stunted and 52 non-stunted (two to five years old) children living in Antananarivo (Madagascar) was performed. Compared to age-matched non-stunted controls, stunted children aged 2-3 years old had a lower relative proportion of classical monocytes. No significant associations were found between stunting and the percentages of effector T helper cell populations (Th1, Th2, Th17, Th1Th17, and cTfh). However, we found that HLA-DR expression (MFI) on all memory CD4+ or CD8+ T cell subsets was significantly lower in stunted children compared to non-stunted controls. Interestingly, in stunted children compared to the same age-matched non-stunted controls, we observed statistically significant age-specific differences in regulatory T cells (Treg) subsets. Indeed, in 2-3 years old stunted children a significantly higher percentage of memory Treg, whilst a significant lower percentage of naive Treg, was found. Our results revealed that both innate and adaptive systemic cell percentages, as well as activation status, were impacted in an age-related manner during stunting. Our study provides valuable insights into the understanding of systemic immune system changes in stunted children.